The Effect of Water Hyacinth Biomass (Eichornia crassipes) on the Concentration of Chlorophyll-a on Local Catfish (Clarias batrachus) Rearing - Simatupang, Deni Efandry; syafiadiman, Syafriadiman; Hasibuan, Saberina (Jurnal Perikanan dan Kelautan, 2023)
Eichornia crassipes have root fibers that can repair water quality, improve the concentration of chlorophyll-a, increase growth, and maintain the survival of local catfish. The purpose of this study was to obtain the best biomass of water hyacinth for the increasing concentration of chlorophyll-a on local catfish rearing in August – September 2020. This study used a one-factor completely randomized design (CRD) with 4 treatments and 3 replication. The treatments in this study had different water hyacinth biomass, P0 (Control), P1 (112 g m-2), P2 (162 g m-2), and P3 (212 g m-2). The local catfish seeds that are used are sized approximately 5-7 cm, weigh 2.62-3.02 g, maintained for 30 days in a rearing container with a peat water volume of 98 L and a density of 2 fish L-1. The result showed that the best treatment was biomass 212 g m2 water hyacinth containing concentration chlorophyll-a 0.73 µg L-1 with the value of correlation concentration chlorophyll-a (r)=0.97 and R2=0.95, it was able to improve concentration chlorophyll-a on local catfish rearing such as increasing pH 5.7-6.0, nitrate 2.45 mg L-1, phosphate 2.09 mg L-1, temperature 27-280C and dissolved oxygen 5.4-5.5 mg L-1. Absolute weight growth (9.04g) with the value of correlation (r) = 0.99 and R2 = 0.99, and survival rate of local catfish (94.67%). The highest growth of the biomass water hyacinth per 3 days is 2.82%.